Exploring the connection between the testing of reading and literacy: the case of the MUET - Lee, King Siong (Penerbit UKM, 2004)
The Malaysian University English Test (MUET), introduced in 1999, is a potentially high-stakes test because of the fact that it is a mandatory requirement for admission into public universities. It was introduced with the aim of bringing about a higher level of English proficiency, especially crucial for those entering university. The paper focuses on the impact of the Reading component on literacy, and examines four factors that are perceived to affect the impact of the MUET, namely: 1) the perceived status of the MUET, 2) the sociopolitical situation, 3) the teacher/teaching, and 4) the test construct. It concludes that the reading construct in the MUET Reading component is inadequately operationalized and suggests that the construct be reviewed in the light of long-term literacy goals.